EXPLORATION OF INDIGENOUS LEAD (PB)-RESISTANT BACTERIA FROM RUBBER WASTEWATER AS CANDIDATES FOR BIOREMEDIATION AGENTS - Putri, Emilya; Febria, Fuji Astuti; Tjong, Djong Hon (Universitas Tanjungpura, 2025)
The presence of heavy metals such as lead (Pb) in rubber processing wastewater originates from coagulant materials, vulcanization processes, and raw water contamination. Pb is toxic and persistent, thus requiring proper treatment. This study aims to isolate indigenous bacteria from rubber wastewater that are resistant to Pb and have potential as bioremediation agents. Isolation was performed using the dilution-pour plate method, with selection on a medium containing Pb(NOâ‚ƒ)â‚‚. Resistance tests were conducted at increasing concentrations (100